Taxonomy, and geographic and ecological distribution of the genus Penstemon (Plantaginaceae) in the Trans-Mexican Volcanic Belt, Mexico - Zacarias-Correa, Ana Gabriela; Guzmán-Díaz, Salvador; Pérez-Calix, Emmanuel (Instituto de Ecología, A.C., 2019)
background and Aims: Penstemon is one of the most diverse genera within Plantaginaceae, with around 283 species occurring from Alaska to Guatemala. At least 50 species are cited in the literature for Mexico; however, until now little is known about their taxonomy, distribution, diversity as well as their conservation status. Due to the richness, the composition and the endemism of the flora of the Trans-Mexican Volcanic Belt, it is considered as an important region to realize a first approximation of the knowledge about the genus Penstemon in Mexico.Methods: Floristic treatments of the Trans-Mexican Volcanic Belt, online databases as well as taxonomic studies of the genus were analyzed, specimens of Penstemon deposited in 12 herbaria in central Mexico were revised and the conservation status of each species was evaluated. In addition, we analyzed the distribution patterns of the Penstemon species from the study area through a quantitative biogeographic study.Key results: We documented and analyzed the distribution patterns of nine taxa of Penstemon for the Trans-Mexican Volcanic Belt. We listed the taxa found as well as valid names, synonyms, morphological descriptions, conservation status, and distribution maps.Conclusions: Although no endemic Penstemon taxa of the Trans-Mexican Volcanic Belt were found, it is important to note that the largest part of the distribution area of five of the nine treated taxa is concentrated in this province. Moreover, it was discovered that the eastern portion of the Trans-Mexican Volcanic Belt is the region where the largest species richness of the studied genus occurs.